2021
DOI: 10.3390/nano11051285
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine as an Irreversible Inhibitor of the Peroxidase-Mimic Catalytic Activity of 2-Dimensional Ni-Based Nanozymes

Abstract: The ability to modulate the catalytic activity of inorganic nanozymes is of high interest. In particular, understanding the interactions of inhibitor molecules with nanozymes can bring them one step closer to the natural enzymes and has thus started to attract intense interest. To date, a few reversible inhibitors of the nanozyme activity have been reported. However, there are no reports of irreversible inhibitor molecules that can permanently inhibit the activity of nanozymes. In the current work, we show the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
2
14
0
Order By: Relevance
“…It has been reported that L‐cysteine can inhibit the enzyme‐like activity of nanomaterials through the interaction of −SH with metal active centers, thus resulting in changes of oxTMB absorbance [44] . Based on this unique mechanism, diverse metal‐based POD‐like nanomaterials have been designed to detect L‐cysteine [44,45] . Due to the excellent POD‐like activity of Cu‐PcCP NPs, the catalytic sensing of L‐cysteine is carefully investigated via TMB mediated POD‐like activity assay (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that L‐cysteine can inhibit the enzyme‐like activity of nanomaterials through the interaction of −SH with metal active centers, thus resulting in changes of oxTMB absorbance [44] . Based on this unique mechanism, diverse metal‐based POD‐like nanomaterials have been designed to detect L‐cysteine [44,45] . Due to the excellent POD‐like activity of Cu‐PcCP NPs, the catalytic sensing of L‐cysteine is carefully investigated via TMB mediated POD‐like activity assay (Figure 7a).…”
Section: Resultsmentioning
confidence: 99%
“…[44] Based on this unique mechanism, diverse metal-based POD-like nanomaterials have been designed to detect L-cysteine. [44,45] Due to the excellent…”
Section: Colorimetric Detection Of L-cysteinementioning
confidence: 99%
“…Following the in-depth characterization of the Co 3 S 4 nanosheets, we first explored their ability to mimic the catalytic activity of the natural peroxidase enzyme. ,,, For this, the ability of Co 3 S 4 nanosheets to convert the colorless diamine TMB to a blue colored charge transfer product (λ max at ca. 650 nm) was assessed following its incubation with peroxidase substrates TMB and H 2 O 2 . , As shown in Figure a, the Co 3 S 4 nanosheets could rapidly oxidize TMB in the presence of H 2 O 2 at initial time points with the activity saturating within 15 min of the reaction.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This reversible binding showed similarity to the enzymatic competitive inhibition process. Subsequently, our more recent work has shown that l -cysteine binds irreversibly to Ni-based NZs . This difference in the mechanism suggested that the composition of the NZ can have a major role in the ability of the NZ to interact with l -cysteine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation